(untitled) (Research, Society and Development, 2018)
Making the right and safe decisions keeps the balance in business. Thus, the present case aims to address the importance of good communication during the decision process in negotiations of the company Azê Confecções. The case reports some unpleasant experiences experienced by employees of the company Azê, experiences that have arisen through failures in communication and search for power. This study was created based on research done on the internet, added to the situations that occurred in knowledge companies of group participants. The main aspects of management used in the reports are: communication failure, conflicts and lack of planning. This study can be recommended for discipline related to communication, leadership, negotiation and action plans.